2004
DOI: 10.1080/01612840490443437
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Appropriate Substance Abuse Treatment for Parenting African American Women

Abstract: Culturally appropriate strategies have been deemed necessary for the treatment of substance abuse among African American women. This qualitative study was conducted utilizing a grounded theory methodology within a womanist theoretical framework to explore the process by which parenting African American women participate in formal substance abuse treatment programs. Study findings yielded significant insights into this process and support the notion that culturally appropriate frameworks are necessary to help s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…Client perceptions that therapists are untrustworthy (Terrell & Terrell, 1984), lack relevant cultural knowledge (Lewis, 2004), and are unable or unwilling to connect (Palmer et al, 2009) weaken the therapeutic relationship and have been identified as obstacles to clients staying in treatment (Bass & Jackson, 1997;Comas-Diaz & Greene, 1994;Sanchez-Hucles, 2001). This is significant because a favorable therapeutic relationship is signifi cantly associated with increased treatment retention (Florentine & Hillhouse, 1999;Hawke, Hennen, & Gallione, 2005;Martin, Garske, & Davis, 2000;Palmer et al, 2009).…”
Section: Treatment Retention and Working Alliancementioning
confidence: 98%
“…Client perceptions that therapists are untrustworthy (Terrell & Terrell, 1984), lack relevant cultural knowledge (Lewis, 2004), and are unable or unwilling to connect (Palmer et al, 2009) weaken the therapeutic relationship and have been identified as obstacles to clients staying in treatment (Bass & Jackson, 1997;Comas-Diaz & Greene, 1994;Sanchez-Hucles, 2001). This is significant because a favorable therapeutic relationship is signifi cantly associated with increased treatment retention (Florentine & Hillhouse, 1999;Hawke, Hennen, & Gallione, 2005;Martin, Garske, & Davis, 2000;Palmer et al, 2009).…”
Section: Treatment Retention and Working Alliancementioning
confidence: 98%
“…Women's addiction has been described as more bsocially embeddedQ than men's (Saunders, Baily, Phillips, & Allsop, 1993). Similarly, qualitative studies concerned with women's recovery hinge on the repair of relationships with children and other family members and on the development of support systems to prevent relapse (Kearney, 1998;Lewis, 2004).…”
Section: Gender-specific Treatmentmentioning
confidence: 98%
“…For women in such groups, issues left unaddressed can result in adverse psychological effects (Copeland & Hall, 1992). Women stress that a treatment environment that is safe for themselves and their children promotes therapeutic effects (Lewis, 2004). Other environmental characteristics, such as comfort, size, privacy, location, and attractiveness, have a small but demonstrable influence on women's engagement in treatment (Grosenick & Hatmaker, 2000).…”
Section: Gender-specific Treatmentmentioning
confidence: 98%
“…In mixed gender groups, women tend to be less verbally expressive and more likely to yield to interruptions than when in same-sex groups (Hodgins et al, 1997), which can result in adverse effects, including dropout (Copeland & Hall, 1992). Women report that a treatment environment in which they feel safe promotes therapeutic effects (Lewis, 2004). A safe and welcoming environment has been deemed essential to the process of change for substance-using women (Curet & His, 2002).…”
Section: Gender-specific Substance Abuse Treatment For Womenmentioning
confidence: 99%
“…For many women, substance abuse offers a means of coping with trauma, such as childhood abuse, partner violence, and, for Aboriginal women, the intergenerational effects alcohol (Comfort & Kaltenbach, 2000;Finkelstein, 1994;McComish et al, 2003). In qualitative studies of females in recovery, women report the importance of repairing relationships with family members and developing social support systems to prevent relapse (Kearney, 1998;Lewis, 2004). In a recent qualitative study of First Nations women in treatment for drug abuse in Canada, social stigma was reported as a significant influence on women's self-identity and on their recovery (Acoose & Dell, 2009).…”
Section: Introductionmentioning
confidence: 99%